Tourism management an introduction - Inkson, Clare; Minnaert, Lynn (SAGE, 2022)
This introductory text provides readers with a robust understanding of tourism and its industries, including how destinations are developed, marketed and managed, and how tourism impacts communities, environments and economies. The authors discuss the critical issues affecting 21st century tourism, such as sustainability, the climate crisis, globalisation, community, technology, the environment and the sharing economy. The text has been fully updated in light of the Covid-19 pandemic and its notable, and in some cases lasting, impacts on the tourism industry.